ANALISIS KINERJA PEMBIAYAAN MURABAHAH PADA PERBANKAN SYARIAH PASCA BERLAKUNYA UNDANG-UNDANG âPENGHAPUSAN PAJAK BERGANDAâ - Utami, Yuni; Mubarok, Abdulloh (PERMANA, 2014)
This study aims to obtain empirical findings regarding: 1. performance growth of Murabaha financing in Islamic banking after the enactment of UU No. 42 tahun 2009. 2. Whether there is a significant difference between the performance of Murabaha financing on Islamic banking before and after the enactment of UU No. 42 tahun 2009. 3. Effectiveness of the implementation of UU No. 42 tahun 2009, especially related to financial performance improvement of Islamic banking. The type of the data is secondary data that is of value (rupiah) Murabaha financing in Islamic banking in each month during the period April 2007 to March 2010 and the period April 2010 to March 2013. 1 April 2010 is the dividing line between the two variables because that date is the date of the enactment of UU No. 42 tahun 2009 on the Third Amendment UU No. 8 tahun 1983 on Value Added Tax on Goods and Services and Sales Tax on Luxury Goods. To test the hypothesis, the research use the statistical test Paired sample t-test. This is because the sample will be compared to the mean is paired samples (paired). The results of this study concluded that there are significant differences between the performance of murabaha financing in Islamic banking before and after the enactment of UU No. 42 tahun 2009. It also shows that the implementation of UU No. 42 tahun 2009 effective enough to improve the performance of Islamic banking, particularly with respect to the performance of murabaha financing.Keywords: Murabaha Financing, UU No. 42 tahun 2009, Islamic Banking, Double Taxation